Structural Design of a 10-Story Office Building using the Special Moment Frame System (SMFS) in Padang, West Sumatra - Yunas, Barkhia; Octavia, Dyla Midya; Syafri, Yuni Purnama; Zayu, Wiwin Putri; Furqoni, Fahma; Ramadhi, Ramadhi; Ernawati, Ernawati (Universitas Negeri Padang, 2024)
Indonesia is located at the convergence of the Eurasian, Pacific, and Indo-Australian tectonic plates, making it prone to significant earthquakes, such as the Aceh earthquake and tsunami in 2004 with a magnitude of 9.1, and the Padang earthquake in 2009 with a magnitude of 7.6, both known for their severe impacts. According to the Central Statistics Agency (BPS), there were 10,843 earthquakes in 2022. Given this high level of risk, all buildings, especially offices, must be designed to be earthquake-resistant due to high activity and user numbers. The city of Padang is categorized in Seismic Design Category D, indicating a high level of earthquake risk. The construction of a ten-story reinforced concrete building for office use is planned, referring to SNI 1726-2019 on earthquake resistance and SNI 1727-2020 on minimum loads, along with the Special Moment Resisting Frame System (SMRF). Structural analysis and modeling are conducted using ETABS software, with element dimensions based on the initial design. This analysis aims to ensure the building meets earthquake resistance requirements through response spectrum evaluation, including natural periods, inter-story drift, P-Delta effects, and checks for irregularities. Based on internal forces from ETABS V.18, reinforcement designs are prepared for structural elements such as columns, beams, slabs, and shear walls. A design capacity evaluation ensures the safety and optimal performance of the structure during an earthquake.